Methods to identify the prey of invertebrate predators in terrestrial field studies. Issue 6 (22nd February 2017) - Birkhofer, Klaus; Bylund, Helena; Dalin, Peter; Ferlian, Olga; Gagic, Vesna; Hambäck, Peter A.; Klapwijk, Maartje; Mestre, Laia; Roubinet, Eve; Schroeder, Martin; Stenberg, Johan A.; Porcel, Mario; et al.
Abstract: Predation is an interaction during which an organism kills and feeds on another organism. Past and current interest in studying predation in terrestrial habitats has yielded a number of methods to assess invertebrate predation events in terrestrial ecosystems. We provide a decision tree to select appropriate methods for individual studies. For each method, we then present a short introduction, key examples for applications, advantages and disadvantages, and an outlook to future refinements. Video and, to a lesser extent, live observations are recommended in studies that address behavioral aspects of predator–prey interactions or focus on per capita predation rates. Cage studies are only appropriate for small predator species, but often suffer from a bias via cage effects. The use of prey baits or analyses of prey remains are cheaper than other methods and have the potential to provide per capita predation estimates. These advantages often come at the cost of low taxonomic specificity. Molecular methods provide reliable estimates at a fine level of taxonomic resolution and are free of observer bias for predator species of any size. However, the current PCR‐based methods lack the ability to estimate predation rates for individual predators and are more expensive than other methods. Molecular and stable isotope analyses are best suited to address systems that include a range of predator and prey species. Our review of methods strongly suggests that while in many cases individual methods are sufficient to study specific questions, combinations of methods hold a high potential to provide more holistic insights into predation events. This review presents an overview of methods to researchers that are new to the field or to particular aspects of predation ecology and provides recommendations toward the subset of suitable methods to identify the prey of invertebrate predators in terrestrial field research. Abstract : We present a decision tree and overview of methods to measure invertebrate predation in terrestrial ecosystems. Major method are addressed with an introduction, examples for applications, a discussion of advantages and disadvantages, and an outlook to future refinements.